Energy Transformation Digital Comic as a Post-Pandemic Learning Recovery Effort in Fourth-Grade Elementary School - Cefa Yonita Salsabila; Dewi Nilam Tyas (Jurnal Pendidikan Indonesia, 2024)
The problem of learning loss due to the COVID-19 pandemic is currently still common in elementary schools. This has an impact on low science learning outcomes for students. This research aims to develop learning media in the form of digital comics as a post-pandemic learning recovery effort. The research method used is the R&D (Research and Development) research method using the Borg & Gall development model. The subjects of this research are material experts and learning media experts. The test subjects for this research were small-scale trials carried out by nine students using purposive sampling techniques and teachers. The test subjects for product effectiveness were 34 students. The methods used to collect data are observation, interviews, questionnaires, and tests. The instruments used to collect data were questionnaire sheets and test questions. The techniques used to analyze data are qualitative, quantitative, and inferential statistical descriptive analysis. The results of this research are digital comic media, which has gone through the revision stage and received high validation scores from media experts and material experts. This media is considered suitable and can be applied in learning and research. After analyzing the N-Gain scores, significant differences were also seen between the pre-test and post-test data, indicating increased students' learning abilities regarding understanding the material in the high category. It was concluded that the digital comics developed could be used to overcome learning loss in elementary schools.